High-velocity low-amplitude manipulation (thrust) and athletic performance: a systematic review - Mikhail Santos Cerqueira; Rafael Moreira Sales; Cláudia Thais Pereira Pinto; Bruno Gonçalves Dias Moreno; Alberto Galvão de Moura Filho (Fisioterapia em Movimento)
Abstract Introduction: The high demand level in sports has encouraged the search for strategies to increase the yield. In this context, manual therapy through high-velocity low-amplitude (thrust) has been employed in many sports. Despite the adhesion of manual therapists in clinical practice, there were no systematic reviews on this topic. Objective: To evaluate the effects of thrust on the performance of athletes in relation to the outcomes hand-grip strength, jump height and running speed. Methods: The databases used in the search were MEDLINE / PUBMED, LILACS, CINAHL, PEDro, WEB OF SCIENCE, CENTRAL and SCOPUS, and Randomized controlled trials were included, whose participants were professionals or recreational athletes and had thrust as intervention. The methodological quality of the studies was assessed using the PEDro scale of 10 points. Intervention effects were determined by the mean difference and confidence interval. The data analysis was done in the descriptive form due to the heterogeneity found among studies. Results: Five trials were included with a total of 95 individuals. The methodological quality of studies was low, with an average value of 5.6 on the PEDro scale. It was found two articles for each outcome, but in none of them was presented differences between the experimental and control groups considering the confidence interval. Conclusion: The current evidence is insufficient to determine the use or nonuse the MAVBA in sports in order to improve performance.